PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CITRA SHIPYARD BATAM - Ade Irmaya Sari Sirait; Sastra Tamami; Edwin Agung Wibowo (BENING, 2017)
The purpose of this research is to identify and analyze the influence of leadership style, motivation and job satisfaction to employees performance at PT. Citra Shipyard Batam. This study using simple random sampling technique and data analysis methods used are validity, reliability test, classic assumption test and multiple regression analysis. As the object of this study are employees of PT. Citra Shipyard Batam sample image with 65 employees as respondents. The technique of collecting data using questionnaires and interviews.   The results obtained from this study indicate that the value of t hitung for the variable of leadership style at 2,086 and significant level of 0,041, value of  thitung for the motivation of 2,576 and a significant level of 0,012, and t hitung for job satisfaction at 7,092 and significant level of 0,000, which is smaller than 0,05. This indicate a positive and significant results to the improved performance of employees at PT. Citra Shipyard Batam. Data variables that most influence in establishing the performance of employees is job satisfaction variables.